(untitled) (Libellarium: journal for research in the field of information and related sciences, 2013)
The paper focuses on the media discourse on reading rooms and libraries as a historical phenomenon that describes the role and place of reading rooms and libraries in Dalmatia in the 60ties of the 19th century and World War I. The papers in Dalmatian newspapers from that period, as materialized forms of discourse, answer many important questions related to the history of Croatian librarianship: how were the reading rooms and libraries established and what crucial concept determined their role and place in a particular period in history. The paper presents the historical concept, conditions in which the discourse occurred, discourse types and functions, conceptual structure, and transformation processes towards new discourse practices. The discourse analysis has shown that the reading rooms and libraries are cultural artifacts strongly influenced by the social context. Two stages in the development of discourse have been identified: in the first stage the discourse takes a considerable role in metaphorical games and construction of mythical structures - ethnic identity, national unity and language community. On the conceptual level the role of reading rooms and libraries is recognized in the deconstruction of traditional relations - they are a territorially separate, exclusive place of symbolic production, creation of new social structures and cultural values. In that context, the activities of libraries are underrepresented compared to other activities of reading rooms. The second stage, which started in the 90ies of the 19th century, is marked by discourse multiplication, differentiation of library organization structure and function from other functions of culture, and the strong influence of new discourse. The media discourse presents the change of conceptual structures, in which the role and place of libraries is interpreted in the context of the role of knowledge and education in meeting society goals in the situation of social differentiation, and need for further construction of modern society and collective subjectivism. By contrast, the main feature of this stage is the strong influence of the knowledge discourse, supported institutionally by the role of libraries in knowledge dissemination.